Research Landscape On Watershed Management In Indonesia; A Bibliometric Analysis - Muh. Sofyan Budiarto; Ida Widianingsih; R. Ahmad Buchari; Entang Adhy Muhtar; Herri Saksono (Aliansi, 2022)
The research goal is to investigate the evolution of watershed management research through an investigative scientific article published by Indonesian researchers in various journals and conferences indexed by Scopus. Scopus publication data was searched using the terms “watershed management" and "Indonesia," and the results were narrowed down by paper type, topic area, and affiliate country. Totally, 181 retrieved articles are then analysed with R Studio and Vos Viewer software for analysis related to bibliometric profile, authorship, co-occurrence, and collaboration. From 1982 to 2021, there was a rise in the number of publications with the topic of watershed management in Scopus indexed journals and proceeding articles. The productivity of publications is increasing. The IOP Conference on Earth and Environment has become the main reference for publications by scholars from Indonesia, with a total of 68 articles published. Bogor Agricultural University is the most productive institutional with 31 articles published. The most productive writers are Arifin (affiliated with University of Lampung) and Suryaatmojo (affiliated with Gadjah Mada University), both of whom had five articles published. Collaborations between authors and nations such as the United States, Canada, and Japan demonstrate the most prevalent research collaborations on relevant topics. In Indonesia, research on the theme of watershed management is still dominant in scientific perspectives such as the environment, forestry, flood control, disaster management, and climate change, so research in other perspectives of blended knowledge, such as public administration, is required for future research.